2019
DOI: 10.1016/j.colsurfb.2019.110411
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun oral formulations for combined photo-chemotherapy of colon cancer

Abstract: In this work, we report new formulations for the combined photo-chemotherapy of colon cancer. Fibers were fabricated via coaxial-electrospinning with the intent of targeting delivery of the anti-cancer drug carmofur (CAR) and the photosensitizer rose bengal (RB) selectively to the colon site. The fibers comprised a hydroxypropyl methylcellulose (HPMC) core loaded with the active ingredients, and a pH-sensitive Eudragit L100-55 shell. The fibers were found to be homogeneous and cylindrical and have visible core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Their encapsulation in Eudragit-based fibres is expected to overcome this issue, with the polymers providing protection from acidic environments due to their lack of solubility at low pH. 31 In order to test their stability, 10 mg of S100/Carmofur/SPION or L100/Carmofur/SPION fibres were incubated in 25 mL of pH 1.5 aqueous HCl solution, similar to the pH of gastric liquids. 32 To compare their acid stability with bare nanoparticles, 2 mg of PVP-SPIONs was subjected to the same treatment.…”
Section: Ph Responsive Propertiesmentioning
confidence: 99%
“…Their encapsulation in Eudragit-based fibres is expected to overcome this issue, with the polymers providing protection from acidic environments due to their lack of solubility at low pH. 31 In order to test their stability, 10 mg of S100/Carmofur/SPION or L100/Carmofur/SPION fibres were incubated in 25 mL of pH 1.5 aqueous HCl solution, similar to the pH of gastric liquids. 32 To compare their acid stability with bare nanoparticles, 2 mg of PVP-SPIONs was subjected to the same treatment.…”
Section: Ph Responsive Propertiesmentioning
confidence: 99%
“…It was confirmed that the fibre improved selectivity for cancerous cells, obviously in the favour of RB. Moreover, targeted treatment was performed by releasing most of the drugs into the colon pH environment, which adhered to the colon wall for over 4 h [ 72 ]. Liu and co-workers built another implantable coaxial composite hydrogel fibre and combined PTT and chemotherapy to control the progression of cancer locally.…”
Section: Coaxial Electrospun Fibres For Combinatorial Therapymentioning
confidence: 99%
“…Li et al (2019b) prepared core/shell fibers by coaxial electrospinning with a hydroxypropyl methylcellulose core and Eudragit L100‐55 shell for combined photochemotherapy in colon cancer. The fiber shells were stable in acidic pH but dissolved in pH 7.4.…”
Section: Drug Deliverymentioning
confidence: 99%
“…Moreover, the photo‐chemotherapy showed greater selectivity for the cancerous cells compared to healthy cells in vitro. In addition, these fibers had excellent adherence to the colon wall which provided substantial ground to do further investigation to treat color cancer via oral administration of carmofur by this technique (Li et al, 2019b).…”
Section: Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation